Action of propolis and medications against Escherichia coli and endotoxin in root canals - Valera, Marcia Carneiro [UNESP]; da Rosa, Jucely Aparecida [UNESP]; Maekawa, Lilian Eiko [UNESP]; de Oliveira, Luciane Dias [UNESP]; Talge Carvalho, Claudio Antonio [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Mosby-elsevier, 2010)
This study evaluated the action of propolis and intracanal medications against Escherichia coli and endotoxin. Forty-eight dental roots were contaminated with E. coli. The root canals were instrumented with propolis and divided into groups according to the type of intracanal medication: Ca(OH)(2), polymyxin B, or Ca(OH)(2) + 2% chlorhexidine gel. In the control group, saline solution was used without application of intracanal medication. Counts of colony-forming units were carried out and the endotoxin was quantified by the chromogenic Limulus amobocyte lysate assay. The results were evaluated by analysis of variance and the Dunn test (5%). Root canal irrigation with propolis was effective to completely eliminate E. coli and reduce the amount of endotoxins. All intracanal medications contributed to the significant decrease in endotoxins. Only intracanal medications may reduce the amount of endotoxins in the root canals. The greatest efficacy was observed for medications containing Ca(OH)(2). (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010;110:e70-e74)